Pengaruh Operating Cash Flow, Investment Activities, Leverage terhadap Corporate Cash Holding - Nurainun Bangun, Lici Millianto, (Jurnal Ekonomi, 2021)
The purpose of this study is to provide empirical evidence whether operating cash flow, investment activities and leverage have an effect on corporate cash holding. This study also aims to test and develop the consistency of the results of previous studies. The population of this study is from the property, real estate and construction sectors which are listed on the Indonesia Stock Exchange for 3 years, namely from 2018 - 2020. The sample in this study was selected by purposive sampling and the data were analyzed using multiple linear regression. The results of this study indicate that operating cash flow and investment activities have a positive effect on corporate cash holding, while leverage has a negative effect on corporate cash holding.